2001
DOI: 10.3346/jkms.2001.16.5.553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Centrally Administered Losartan on Deoxycorticosterone-salt Hypertension Rats

Abstract: INTRODUCTIONIn deoxycorticosterone acetate (DOCA)-salt hypertensive rats the development and maintenance of hypertension is considered to be independent of the renin-angiotensin system, because plasma renin in this model is low (1), and peripheral administration of angiotensin converting enzyme (ACE) inhibitors (2) or angiotensin (Ang) II receptor antagonists (3) has no effect on blood pressure (BP). However, there is some evidence for a role of the brain renin-angiotensin system in the pathogenesis of DOCA-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 27 publications
1
40
1
Order By: Relevance
“…[23][24][25][26] Consistent with our hypothesis, we found that induction of a hypertensive state was associated with a decrease in the levels of hypothalamic ␥-adducin. However, in contrast to genetic models, ␥-adducin levels in the brainstem did not change in both nongenetic rat models.…”
Section: Discussionsupporting
confidence: 88%
“…[23][24][25][26] Consistent with our hypothesis, we found that induction of a hypertensive state was associated with a decrease in the levels of hypothalamic ␥-adducin. However, in contrast to genetic models, ␥-adducin levels in the brainstem did not change in both nongenetic rat models.…”
Section: Discussionsupporting
confidence: 88%
“…Porter et al have demonstrated that ICV infusion of angiotensin II causes increased energy expenditure in both young and old rats [31,32]. Chronic delivery of DOCA-salt results in hypertension that depends upon increased activity of the brain RAS, as ICV infusion of the ACE inhibitor captopril or the AT1 antagonist losartan prevent and reverse DOCA-salt hypertension [71][72][73]. Similarly, ICV infusion of losartan attenuates the resting metabolic rate increase that occurs with DOCA-salt [74].…”
Section: The Brain Ras and Energy Outputmentioning
confidence: 91%
“…The DOCA-salt model (deoxycorticosterone acetate plus a high dietary sodium load) of hypertension is a well-established model of low-renin hypertension mechanistically involving brain ANG II and AT 1A receptors (16)(17)(18). It is notable that DOCAsalt also robustly stimulates RMR, an effect that also requires brain AT 1A receptors (19).…”
Section: Resultsmentioning
confidence: 99%